The effect of political risk on shareholder value and the mitigating role of corporate social responsibility (CSR) - Chatjuthamard, Pattanaporn; Jiraporn, Pornsit; Sarajoti, Pattarake; Singh, Manohar (Managerial Finance, 2020)
Purpose: The study investigates the effect of political risk on shareholder value, using an event study and a novel measure of firm-level political risk recently developed by Hassan et al. (2017). In addition, the authors explore how corporate social responsibility (CSR) influences the effect of political risk on shareholder wealth. Design/methodology/approach: The authors exploit the guilty plea of Jack Abramoff, a well-known lobbyist, on January 3, 2006, as an exogenous shock that made lobbying less effective and less useful in the future, depriving firms of an important tool to reduce political exposure. Findings: The results show that the market reactions are significantly more negative for firms with more political exposure. Additional analysis corroborates the results, including propensity score matching, instrumental-variable analysis and Oster's (2019) method for testing coefficient stability. Finally, the authors note that the adverse effect of political risk on shareholder value is substantially mitigated for firms with strong social responsibility, consistent with the risk mitigation hypothesis. Originality/value: This study is the first to explore the effect of political risk on shareholder value using a novel measure. Furthermore, it is also the first to show that CSR alleviates the cost of political risk to shareholders. © 2020, Emerald Publishing Limited.
Keywords: CSR; Corporate social responsibility; Event study; Firm risk; G34; M14; Political risk; Shareholder wealth; dept.fin; dept.grad; peer-reviewed

CEO characteristics, firm performance, and corporate political contributions - Subrahmanyam, Vijaya; Singh, Manohar; Pennathur, Anita K. (Review of Financial Economics, 2020)
We investigate if CEO characteristics determine the choice of Political Action Committee (PAC) contributions by firms and if such participation leads to better firm performance. Using a unique, hand-collected database, we also focus on the identity of the politicians receiving PAC contributions to examine the impact of the value-relevance of such contributions. Examining data on corporate contributions made to candidates seeking federal office during the 2002, 2004, and 2006 election cycles, we find that CEO dominance and interest alignment influence strategic choices of firms with regards to establishing PACs. Our analysis of value-relevant contributions shows that firms prefer to donate to politicians representing the state of a firm's headquarters, validating the truth to the adage that all politics is local. However, these targeted political contributions do not have a discernible impact on firm performance.
Keywords: CEO characteristics; CEO dominance; agency theory; corporate political contributions; dept.fin; dept.grad; firm performance; peer-reviewed